Environmental and behavioural factors associated with Mycobacterium ulcerans infection in the district of Lalo in Benin: A case-control study - JOHNSON, ROCH CHRISTIAN; Sopoh, Ghislain Emmanuel; Barogui, Yves Thierry (My University, 2021)
The mode of transmission of Buruli ulcer (BU) is not yet well understood. This study aimed to identify risk factors for BU in the district of Lalo in Benin. This is a case-control study taking into account all cases of BU detected from 2013 to 2018 and treated at the Buruli’s ulcer Screening and Treatment Center (CDTUB) of Lalo. For each case, two controls were matched according to age and sex. Conditional logistic regression was used to compare risk factors in cases and controls. A total of 59 BU cases and 118 controls were enrolled. After adjustment for potential confounding factors, illiteracy (adjusted odd ratio [aOR] = 18.19; 95% confidence interval [CI] = 1.50-219.45), unawareness of BU risk factors (aOR = 48.21; 95% CI = 4.67-497.15), bathing in rivers or ponds (aOR = 23.66; 95% CI= 2.82- 198.52), field activities in mud (aOR = 60.58; 95% CI = 7.44 – 493.09) and not wearing protective clothing during field activities (aOR = 42.78; 95% CI = 2.05 – 892.33) were associated with BU. It is necessary to mitigate risk factors by implementing actions in the field of water, sanitation and hygiene (WASH) and by insisting on the wearing of protective equipment during agricultural activities and/or contact with surface water.
Keywords: Buruli ulcer; Mycobacterium ulcerans; risk factors; case-control study; Lalo.; INTRODUCTION